Pemikiran ekonomi Islam pada masa dinasti Umayyah: Kebijakan reformasi agraria yang diterapkan oleh dinasti Umayyah di Andalusia - Tisah, Lailatut (Maliki Interdisciplinary Journal, 2023)
At the beginning of the arrival of the Umayyad Dynasty in Andalusia, agriculture in the region faced problems. Land is not being utilized properly and there is an imbalance between food demand and agricultural production. To overcome this, the Umayyad Dynasty implemented agricultural reform policies. The main goal is to increase agricultural production by using more efficient techniques, cultivating diverse crops, and sophisticated irrigation systems (Solehah, 2022). The Umayyad dynasty wanted to build an image of power and glory by increasing agricultural production and creating economic wealth. Overall, the agrarian policy of the Umayyad Dynasty in Andalusia focused on managing the agricultural sector as a source of wealth and power, as well as maintaining social stability and gaining political support (Aravik & Tohir, 2020).